HPLC method development for fampridine using Analytical Quality by Design approach - Kovács Béla; Boda Francisc; Fülöp Ibolya; Székely-Szentmiklósi István; Kelemen Éva Katalin; Kovács-Deák Boglárka; Székely-Szentmiklósi Blanka (Acta Pharmaceutica)
Offering a systematic and multivariate analysis of the analytical procedure, development and validation of HPLC methods using Quality by Design approach are in the limelight of current research trends. A new, experimental design-aided HPLC method for fampridine was developed and preliminarily validated according to current in-force international guidelines for linearity, accuracy, robustness and precision.